Affect- and Cognition-Based Trust as Foundations for Interpersonal Cooperation in Organizations - McAllister, Daniel J. (Academy of Management Journal, 1995)
This study addressed the nature and functioning of relationships of interpersonal trust among managers and professionals in organizations, the factors influencing trust's development, and the implications of trust for behavior and performance. Theoretical foundations were drawn from the sociological literature on trust and the social-psychological literature on trust in close relationships. An initial test of the proposed theoretical framework was conducted in a field setting with 194 managers and professionals.